Pemakaian Fine Coarse Aggregate Sebagai Bahan Paving Tahan Aus (Fine Coarse Aggregate Usage As Raw Materials Of Abrasion Resistant Paving) - Erwin Rommel Rommel (Media Teknik Sipil, 2011)
Paving blocks are widely used in pavement construction such as container terminals, highways, parking lots, other open areas. Ease of installation, low maintenance and meet of the aestethics aspect cause more paving blocks of preferred. The FCA (fine coarse aggregate) paving blocks has the advantage in a mixture of 1:4:3, which is made by full-pressing method at 100 kg/cm2 with a strength reaches 406 kg/cm2 (grade-1); impact resistance is the best on the mixture of paving the heering-bone pattern. This further research will look at the quality aspects of paving from the abrasion resistance and the absorption rate of FCA paving blocks to provide paving mixture variables in (1; 4; 0, 1; 4; 3, 1; 4; 5) and the amount of pressing (60; 80 and 100 kg/cm2). The research results obtained minimum the abrasion resistance obtained at the paving 1; 4; 3 is given pressing 100 kg/cm2, abrasion value of 0.046 mm / min on a top layer of paving using admixture 1; 2 and 0.089 mm / min on without a top layer of paving blocks. The best absorption levels obtained at the paving with the same composition but at 60 kg/cm2 pressing provision.Key-word : pressing, strength, abrasion resistance